Efeito do geraniol no comportamento e no padrão de ondas cerebrais de ratos - Medeiros, Katty Anne Amador de Lucena (2015)
natural molecules found in essential oils, Geraniol is one that has been extensively studied. The literature shows geraniol as an anti-inflammatory, chemo-preventive, antimicrobial, antioxidant, and neuro-protective agent. However, a lack of studies remains in covering the influence of this compound on the central nervous system. This study aimed to characterize the effect of geraniol in brainwave patterns, motor and anxiety-like behavior in Wistar rats. In the experiments, we used one hundred and eighty (180) male Wistar rats, all of them aged 3 and 4 months, from the Central Biotery and Neurophysiology Laboratory Biotery, both of Federal University of Sergipe. Behavioral tests were performed to evaluate engine components and anxiety (perforated plate and open field). We also evaluated barbiturate-induced sleeping time. We performed Electrocorticogram (ECoG) exams to characterize the pattern of brain waves. We used three different doses of geraniol in the tests: 25, 50 and 100 mg/kg. Divergences in the literature regarding the anxiolytic dose of diazepam as control in the hole-board and open field test led us to carry out a dose-response curve to determinate such dose, followed by a comparison with doses of geraniol. In the hole-board we observed that the dose of 2,0 mg/kg Diazepam increased immobility time and decreased the number and duration of rearing. There was a large increase in head-dipping time in animals treated with diazepam 0,5 mg/kg. As to the open field test, Diazepam at a dose of 5,0 mg / kg decreased distance traveled and the animals treated with this dose remained most of the time immobile. The number and duration of rearing were higher in animals treated with diazepam at a dose of 1,5 mg/kg and reduced with Diazepam 5,0 mg/kg. When testing geraniol at doses of 25, 50 and 100 mg/kg in the two apparatuses mentioned we noticed that the dose of 100 mg/kg decreased the distance traveled, the number and duration of rearing, the number and duration of head-dipping and increased immobility time in the hole-board compared to the control groups (saline and Diazepam 0,5 mg/kg). Similarly, in the open field, we observed that animals treated with geraniol (50 or 100 mg/kg) also reduced the distance traveled, the number and duration of rearing, and increased immobility time compared to the saline group and Diazepam 1,5 mg/kg . In the barbiturate-induced sleeping time test, Geraniol (100 mg/kg) did not affect sleep latency, however, increased sleep time of the animals similarly to the animals treated with diazepam 5 mg/kg. Furthermore, Geraniol (100 mg/kg) significantly increased the relative power ECoG of ultra-slow waves (0,5-1,5 Hz) and delta waves (0,5 4,0) and reduced of alfa waves (8,0-13,0 Hz). According to all gathered data, we conclude that geraniol (100 mg/kg) behaves as a hypnotic-sedative drug.